Pathways to improve health information systems in Ethiopia: current maturity status and implications - Amanuel Biru; Dawit Birhan; Gemechis Melkamu; Abebaw Gebeyehu; Afrah Mohammedsanni Omer (BMC, 2022)
Abstract Background To achieve national and international strategic goals, countries are advised to assess the maturity status of their health information systems (HIS), including business continuity and interoperability. This work aims to determine the existing maturity status of the Ethiopian HIS, set HIS improvement goals, and inform a path towards an improved national HIS by the end of 2024. Methods This assessment was a collaborative and transparent process that was carried out with the engagement of all key stakeholders through consultation. We used the Stages of Continuous Improvement (SOCI) tool to guide the assessment to measure the maturity level of the Ethiopian HIS in five core domains, 13 components and 39 subcomponents and to guide future plans. Results The overall average score of the national HIS maturity was 2.68/5, which is categorized between repeatable (stage 2) and defined (stage 3) maturity levels. The assessment findings revealed that three out of the five HIS maturity domains were at a repeatable stage. Only the leadership and governance and the data quality and use domains were at the defined maturity level. A majority (7/13) of the subcomponents were at the repeatable level of maturity, while four were at the defined level. Policy, legal and regulatory framework and compliance from the leadership and governance domain and interoperability from the data quality and use domain were categorized as having an emerging status. Considering the current HIS maturity status, gaps and strengths identified, ongoing HIS initiatives, existing platforms, and the interest and level of engagement of senior government leadership, this assessment put forward an improvement roadmap for achieving the desired managed stage (4.37) of maturity by the end of 2024. Conclusions The findings show that the overall maturity level of the Ethiopian HIS is 2.68, which is between the repeatable and defined maturity stages. Enforcement of policies and legislation, data exchange among systems, and information and communication technology infrastructure business continuity planning are the main challenges of Ethiopian HIS requiring further investment. Strengthened and collaborative effort is critical to reaching the desired goal of "managed" HIS (stage 4) in the country by 2024.